Improving environmental health: investigations into soil lead and phosphorus fate and transport - Weeks, Joseph J. (Kansas State University, 2019)
Phosphorus (P) fertilizer use efficiency can be poor in calcareous and acid soils as a result of fixation reactions that occur between the orthophosphate anion and various forms of calcium (Ca), iron (Fe) or aluminum (Al). To overcome these reactions and prevent P deficiency, growers with access to fertilizers may apply more than the crop will remove. This may create a surplus of P in soil over time that is not highly labile but can still erode or leach into nearby waterbodies jeopardizing drinking water quality, recreational activities, and the of health aquatic wildlife. Where fertilizer access is limited by economic/political forces, ineffective P use manifests as low yields keeping destitute farmers stuck in a cycle of poverty. In both situations, simple, cheap techniques are required to get more “bang for the buck” out of P sources of fertility. One of the main objectives of this lab-based project was to investigate methods to improve plant recovery of applied P. Use of Petri dish incubations allowed for spatial inquiry of P fate and transport in mildly calcareous soils from Finney County, Kansas and an acidic Ultisol from São Paulo, Brazil. Treatments to prevent precipitation and inner-sphere complexation of P when applied as liquid fertilizers included co-application of commercially available humic substances, adjustment of application volume, and blending ortho- and polyphosphates. Anion exchange resin extractability as a percent of total P assessed potential plant availability, total elemental determination evaluated P diffusion, and synchrotron-based X-ray absorption near-edge structure (XANES) spectroscopy was implemented to probe reaction products and pathways along with a suite of other wet chemical analyses. Treatment efficacy was variable and soil specific. Blending ortho/polyphosphates and adjustment of application rate show promise for improving the plant recovery of P added to calcareous soils but not acid, while the impact of co-application of humic substances remains inconclusive. What is certain is that the future of P management will be to more specifically tailor P applications to soil conditions and crop requirements to minimize P loss and/or partitioning to unintended environmental pools and maximize plant uptake. Another threat to human well-being related to the food system is soil contamination with trace elements such as lead (Pb). Urban gardening has been experiencing increasing popularity around the United States spurring a flush of research not only investigating the best growing techniques but also exploring areas of potential human health concern when these gardens are established on brownfields. Three pathways of exposure are typically cited for these soil Pb to enter the human body: ingestion of soil directly, consumption of produce containing or superficially contaminated with a hazardous substance and inhalation of soil dust. The contribution of the inhalation route has not been adequately investigated. An activity-based inhalation risk study was carried out in two urban soils located in Kansas City, MO by collecting dust while garden plots were rototilled. Although the study has been limited to one geographic area, very little dust was collected suggesting that inhalation is not a major exposure pathway for gardeners.
Keywords: Phosphorus; Fertilizer; Soil fertility; Lead; Brownfields; Urban gardening